Optimizing Art and Design Education Through Mobile Apps Development - Abednego, Victor Adiluhung; Kusumawati, Yudhistya Ayu; Christyanti, Michelle Gita (Institut Bisnis dan Teknologi Indonesia, 2024)
The rapid growth of the Visual Communication Design sector in the digital era highlights the increasing demand for skilled graphic designers across various industries. As creative professionals, graphic designers are tasked with conveying messages through visual means, balancing aesthetics, functionality, and technical expertise. However, many designers face challenges in producing high-quality work due to limited practical and theoretical knowledge. This research proposes the development of